Impact of pathological tumor stage for salvage radiotherapy after radical prostatectomy in patients with prostate-specific antigen < 1.0 ng/ml - Umezawa Rei; Ariga Hisanori; Ogawa Yoshihiro; Jingu Keiichi; Matsushita Haruo; Takeda Ken; Fujimoto Keisuke; Sakayauchi Toru; Sugawara Toshiyuki; Kubozono Masaki; Narazaki Kakutaro; Shimizu Eiji; et al. (Radiation Oncology, 2011)
Abstract Background To evaluate prognostic factors in salvage radiotherapy (RT) for patients with pre-RT prostate-specific antigen (PSA) < 1.0 ng/ml. Methods Between January 2000 and December 2009, 102 patients underwent salvage RT for biochemical failure after radical prostatectomy (RP). Re-failure of PSA after salvage RT was defined as a serum PSA value of 0.2 ng/ml or more above the postradiotherapy nadir followed by another higher value, a continued rise in serum PSA despite salvage RT, or initiation of systemic therapy after completion of salvage RT. Biochemical relapse-free survival (bRFS) was estimated using the Kaplan-Meier method. Multivariate analysis was performed using the Cox proportional hazards regression model. Results The median follow-up period was 44 months (range, 11-103 months). Forty-three patients experienced PSA re-failure after salvage RT. The 4-year bRFS was 50.9% (95% confidence interval [95% CI]: 39.4-62.5%). In the log-rank test, pT3-4 (p < 0.001) and preoperative PSA (p = 0.037) were selected as significant factors. In multivariate analysis, only pT3-4 was a prognostic factor (hazard ratio: 3.512 [95% CI: 1.535-8.037], p = 0.001). The 4-year bRFS rates for pT1-2 and pT3-4 were 79.2% (95% CI: 66.0-92.3%) and 31.7% (95% CI: 17.0-46.4%), respectively. Conclusions In patients who have received salvage RT after RP with PSA < 1.0 ng/ml, pT stage and preoperative PSA were prognostic factors of bRFS. In particular, pT3-4 had a high risk for biochemical recurrence after salvage RT.